2004
DOI: 10.1007/s11661-004-0296-0
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum accumulation at ferrite: Austenite interfaces during isothermal transformation of an Fe-0.24 pct C-0.93 pct Mo alloy

Abstract: A scanning transmission electron microscope (STEM) technique was used to measure Mo concentrations at ferrite:austenite (␣:␥) interfaces in an Fe-0.24 pct C-0.93 pct Mo alloy partially transformed at 650°C, 630°C, and 610°C. These concentrations were quite small at 650°C, which is just below the bay temperature of the time-temperature-transformation (TTT) curve for the initiation of ferrite formation. There were larger concentrations at 630°C, a temperature at which transformation stasis (incomplete transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…In the companion article in this symposium, [8] an STEM technique [59,[114][115][116] was used to evaluate Mo enrichment at ␣:␥ boundaries in an Fe-0.24 pct C-0.93 pct Mo alloy as a function of isothermal reaction time at 650°C (just below the bay temperature), 630°C, and 610°C. The overall reaction kinetics at the two higher temperatures were previously investigated.…”
Section: Influence Of X Upon Growth Kinetics Of Ferrite Allotriomorphmentioning
confidence: 99%
See 2 more Smart Citations
“…In the companion article in this symposium, [8] an STEM technique [59,[114][115][116] was used to evaluate Mo enrichment at ␣:␥ boundaries in an Fe-0.24 pct C-0.93 pct Mo alloy as a function of isothermal reaction time at 650°C (just below the bay temperature), 630°C, and 610°C. The overall reaction kinetics at the two higher temperatures were previously investigated.…”
Section: Influence Of X Upon Growth Kinetics Of Ferrite Allotriomorphmentioning
confidence: 99%
“…Root-mean-square diffusion calculations, made under the assumption that segregation occurred from ferrite, where diffusion is much more rapid than in austenite, [117] supported this deduction. Despite the ability of the STEM technique used to detect Ͻ2 pct of a monolayer of Mo enrichment, [6,8] a rough estimate of the number density of kinks on the risers of growth ledges indicated that this technique cannot reveal Mo accumulation at these sites. As noted in Section IV-A of the companion article, [8] it appears that these are the only viable sites for atomic attachment at partly coherent boundaries between crystals whose stacking sequence differs.…”
Section: Influence Of X Upon Growth Kinetics Of Ferrite Allotriomorphmentioning
confidence: 99%
See 1 more Smart Citation
“…In high strength low alloyed steels Mo is well known to provide phase balance strengthening, via facilitating the bainite transformation [1][2][3][4][5], and solid solution strengthening [6][7][8][9]. It can decrease the rate of dynamic recrystallization of austenite [10][11][12], which may lead to grain refinement.…”
Section: Introductionmentioning
confidence: 99%
“…Interphase boundaries, in contrast, have received relatively little attention from experimentalists. [3][4][5][6][7][8] It is the purpose of this contribution to report results of studies of alloying element (Mn) distributions in the vicinity of (quenched) interfaces of grain boundary nucleated proeutectoid ferrite crystals, formed under substitutional solute partitioning conditions in a Fe-0.37C-3.0Mn-1.9Si steel. A lower carbon version of the same alloy was the subject of a previous study of ferrite growth and Mn accumulation at a/c interfaces, initially growing under nonpartitioning conditions.…”
mentioning
confidence: 99%